Principles of Fact-Finding in Criminal Investigations : A Legal Study Under The Thai Criminal Procedure Code - Chaiyapong, Akkakorn; Yimsai, Natthanicha (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2025)
Fact-finding in criminal investigations is a crucial process in the criminal justice system. Its objective is to collect accurate and complete evidence that can lead to fair decisions. These principles are based on legal foundations and procedural frameworks that guide investigators to conduct impartial, transparent investigations while protecting the rights of the accused. The investigative process relies on physical evidence, witness testimony, documents, and scientific evidence. Key principles include the impartiality of investigators, the accuracy of evidence collection processes, and the protection of rights for all involved parties. Furthermore, effective investigations require specialized techniques in analyzing empirical data to ensure that the fact-finding process can discover truth accurately and reliably. This study focuses on analyzing fact-finding principles in criminal investigations, both in theory and practice, as well as identifying obstacles to effective investigations. The goal is to develop the investigative system to be more just and better aligned with human rights principles.